Incidence and risk factors of infections following kidney transplantation - Nouf E Alotaibi (Elsevier, 2024)
Background: For patients with End-Stage Renal Disease (ESRD), kidney transplantation stands as the superior alternative to dialysis, exhibiting enhancements in both quality of life and survival rates. The objective of this study is to ascertain the prevalence of infections and associated risk factors within the initial two years post-renal transplant. Method: A retrospective study of all renal transplant recipients who underwent renal transplantation at king Abdullah medical city in Makkah, Saudi Arabia from January 1st, 2018, till end of December 2021 followed up for two years. Results: A total of 43 patients were included in the study, The participants who experienced infectious episodes had a higher mean age, averaging 45.26 ± 14, in contrast to those who did not, averaging 38.75 ± 12. Most of the patients included in the study were male, 70 % of the total population. However, most infectious complications occurred in women (77 % vs. 30 %, respectively, p-value 0.004). Regarding the mode of dialysis before the transplantation, most of the patients were maintained on hemodialysis (76.7 %), and the mean duration of dialysis was longer on those presented with infections within two years post-transplant compared to those without it (3.26 ± 1.6 vs. 2 ± 1.14 years respectively). The incidence of the infections was 44.2 % (19 individuals). The most common presented infections in the patients within two years post renal transplant were urinary tract infections (20.9 %), with a high recurrence rate reaching 11.6 %. This was followed by Coronavirus disease (COVID-19) and Cytomegalovirus (CMV). Conclusion: This study sheds light on the prevalence of infectious complications following renal transplantation and highlights specific risk factors associated with these infections. Understanding these patterns can aid in the development of preventive strategies and optimized care for transplant recipients during the early post-transplant period.